Optic neuropathy in sarcoidosis. Issue 7 (July 1986) - Graham, E M; Ellis, C J; Sanders, M D; McDonald, W I
Abstract : Five patients with isolated optic neuropathy and sarcoidosis are discussed. The spectrum of clinical disease was variable but two groups could be identified: patients with chronic progressive visual loss which was associated with thickening of the optic nerve and was refractory to steroid treatment, and patients with acute or subacute optic neuropathy in which the visual loss responded rapidly to steroids. In the latter group steroid dependence developed in all three of the patients. In none did the clinical picture resemble that of the optic neuritis associated with multiple sclerosis.